Control of revenue waiver by the Federal Court of auditors in the light of the principle of effectiveness - Garcia , Fernando Augusto Matte (Seven Editora, 2024)
Revenue waivers, or tax expenditures, are as old as taxation itself. The objective is to carry out a theoretical debate on the control of revenue waiver by the Courts of Auditors in the light of the principle of effectiveness. For this, a bibliographic study was carried out in order to understand the different theoretical dialogues of the authors who deal with the theme in question. For this, articles, books, thesis, dissertations, in the databases of Google Scholar, SciELO, CAPES thesis and dissertation database and the TCU platform were consulted. Revenue waiver is the act in which the public manager grants incentives or benefits of a tax, financial and credit nature to citizens. Since the waiver of revenue is justified by the intention to move the action of the agents who choose to adopt this or that conduct, taking into account, among other factors, the reduction of the tax burden that would normally be imposed on them, the efficiency of the tax policy depends on the capacity of the measure to, in practice, induce the behavior of individuals. It is concluded that despite the benefits reaped by the rulers, they must observe that the act of renouncing revenues must be accompanied by the compensatory legal measures provided for this purpose, under penalty of such act not being validated by the national legal system. DOI:https://doi.org/10.56238/sevened2024.010-005